Description of two new species of Arcania Leach, 1817, from the western Pacific Ocean and redescriptions of A. undecimspinosa De Haan, 1841, and A. elongata Yokoya, 1933 (Crustacea: Brachyura: Leucosiidae) - Naruse, Tohru (Zootaxa, 2014)
Arcania undecimspinosa De Haan, 1841, and A. elongata Yokoya, 1933, are redescribed, with a lectotype of A. undecimspinosa formally designated. Redescription of the two species revealed that there are several specimens and possible undescribed species that have been inaccurately recorded under the name of A. undecimspinosa and A. elongata. Two such species are described from the western and southern Pacific Ocean as new to science. These four species partially overlap their geographical distributions and are superficially similar to each other, but the present study shows that there are clear differences in the shapes of their male first gonopods, female vulvae, frontal lobes of the carapace and other morphological characters. Literature that cited A. undecimspinosa s.l. is also reviewed to highlight possible taxonomic problems.